Composite material and preparation method thereof, negative electrode current collector, metal battery and electric device

By using composite materials, including MXene materials, silver nanoparticles and modified bacterial cellulose, as the negative electrode current collector of lithium metal batteries, the problem of battery performance degradation caused by lithium dendrites is solved, and higher electrochemical performance and cycle life are achieved.

CN119601669AActive Publication Date: 2025-03-11NATIONAL INSTITUTE OF GUANGDONG ADVANCED ENERGY STORAGE CO LTD

Patent Information

Application Number
CN202411818160.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-11
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

The formation of lithium dendrites in lithium metal batteries leads to degradation of battery performance, including battery short circuit, low Coulomb efficiency and short cycle life.

Method used

A composite material is used as the negative electrode current collector, including MXene material, silver nanoparticles and modified bacterial cellulose. MXene material is prepared by etching the MAX material and silver nanoparticles are grown in situ on the surface of its sheet layer. The modified bacterial cellulose is modified by lye and loaded on the surface of the MXene material.

Benefits of technology

The composite material has excellent lithium-philic properties, delays the formation of lithium dendrites, improves the electrochemical performance of lithium metal batteries, enhances mechanical properties, optimizes the interface between the negative electrode current collector and the active substance, and improves the cycling performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601669A_ABST
    Figure CN119601669A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of secondary batteries, in particular to a composite material and a preparation method thereof, a negative electrode current collector, a metal battery and an electric device. The composite material provided by the invention comprises an MXene material, and the MXene material comprises a surface functional group; the silver nanoparticles are grown on the surface of the sheet layer of the MXene material in situ; the modified bacterial cellulose comprises bacterial cellulose and oxygen-containing functional groups modified on the surface of the bacterial cellulose; the modified bacterial cellulose is loaded on the surface of the MXene material; wherein the loading mode of the modified bacterial cellulose at least comprises intermolecular interaction between an oxygen-containing functional group of the modified bacterial cellulose and a surface functional group of the MXene material. The composite material provided by the invention has excellent lithium-loving performance, and can delay the formation of lithium dendrites, so that the electrochemical performance of the metal battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to composite materials and preparation methods thereof, negative electrode current collectors, metal batteries, and electrical devices. Background Art

[0002] With the development of electronic devices, electric vehicles and portable power devices, people have higher and higher requirements for battery energy density. Lithium metal batteries have a high theoretical specific capacity (3860mAh g -1 ), low density (0.53 g cm -3 ) and extremely low electrochemical potential (-3.04 V vs standard hydrogen electrode), the lithium metal anode has been considered to be a highly promising secondary battery.

[0003] At present, the negative electrode widely used in lithium metal batteries is lithium metal sheet. During the battery cycle, lithium is deposited on the copper surface to form lithium dendrites. The dendrites continue to grow and pierce the diaphragm, causing battery short circuit, low coulomb efficiency, short cycle life, etc., and may even cause safety problems. Summary of the invention

[0004] Based on this, the present application provides a composite material and a preparation method thereof, a negative electrode current collector, a metal battery, and an electrical device. When the composite material provided in the present application is used as a negative electrode current collector, it has excellent lithium affinity, which can delay the formation of lithium dendrites, thereby helping to improve the electrochemical performance of lithium metal batteries.

[0005] In a first aspect of the present application, a composite material is provided, comprising:

[0006] A MXene material comprising surface functional groups;

[0007] Silver nanoparticles, the silver nanoparticles are in-situ grown on the surface of the MXene material layer;

[0008] Modified bacterial cellulose, wherein the modified bacterial cellulose comprises bacterial cellulose and oxygen-containing functional groups modified on the surface of the bacterial cellulose; the modified bacterial cellulose is loaded on the surface of the MXene material;

[0009] Wherein, the loading method of the modified bacterial cellulose at least includes: intermolecular interaction between the oxygen-containing functional groups of the modified bacterial cellulose and the surface functional groups of the MXene material.

[0010] In one embodiment, the composite material has one or more of the following characteristics:

[0011] (1) The general chemical formula of the MXene material is M n+1 Xn T x , where M is a transition metal element, X is carbon or nitrogen, and T x is a surface functional group, n is 1, 2 or 3, and the surface functional group includes at least one of -OH, -F and =O;

[0012] (2) In the composite material, the mass ratio of the MXene material to the modified bacterial cellulose is 10:(0.1-10);

[0013] (3) In the modified bacterial cellulose, the oxygen-containing functional group includes at least one of -OH and =O.

[0014] A second aspect of the present application provides a method for preparing a composite material, comprising the following steps:

[0015] Under stirring conditions, the MAX material is etched with an etchant to prepare a MXene solution;

[0016] The MXene solution and silver nitrate are mixed, and the silver ions undergo a reduction reaction on the surface of the MXene material sheet, so that silver nanoparticles are in situ grown on the surface of the MXene material sheet, thereby preparing a silver-loaded MXene solution;

[0017] The bacterial cellulose is modified by an alkali solution to prepare a modified bacterial cellulose solution; wherein the surface of the modified bacterial cellulose includes oxygen-containing functional groups;

[0018] The silver-loaded MXene solution and the modified bacterial cellulose solution are mixed, and the modified bacterial cellulose is loaded on the surface of the MXene material to prepare the composite material.

[0019] In one embodiment, the step of preparing the MXene solution further comprises:

[0020] Mixing fluoride salt and hydrochloric acid to prepare the etchant;

[0021] Wherein, the mass volume ratio of the fluoride salt and the hydrochloric acid is 1g: (10-20)mL.

[0022] In one embodiment, the step of preparing the MXene solution has one or more of the following characteristics:

[0023] (1) The fluoride salt includes one or more of lithium fluoride, sodium fluoride and potassium fluoride;

[0024] (2) The molar concentration of the hydrochloric acid is 6 mol / L to 12 mol / L;

[0025] (3) The general chemical formula of the MAX material is Mm+1 AX m , wherein M is a transition metal element, A is a main group element of group IIIA or group IVA, X is carbon or nitrogen; m is 1, 2 or 3;

[0026] (4) The mass ratio of the fluoride salt included in the etchant to the mass ratio of the MAX material is 1:(0.8-1.5);

[0027] (5) After the etching step, the method further includes: centrifuging and washing the mixed solution after the etching, collecting the solid phase, dispersing the solid phase in a dispersant, collecting the supernatant, and preparing the MXene solution.

[0028] In one embodiment, the step of preparing the silver-loaded MXene solution has one or more of the following characteristics:

[0029] (1) In a solution formed by mixing the MXene solution and silver nitrate, the mass concentration of the silver nitrate is 0.3 mg / mL to 1 mg / mL;

[0030] (2) The process parameters of the reduction reaction include: a stirring speed of 50 r / min to 300 r / min.

[0031] In one embodiment, the step of preparing the modified bacterial cellulose solution has one or more of the following characteristics:

[0032] (1) The alkali solution includes one or more of KOH and NaOH;

[0033] (2) The molar concentration of the alkali solution is 0.8 mol / L to 1.5 mol / L;

[0034] (3) The process parameters of the modification treatment include: the modification temperature is 40°C~90°C.

[0035] In a third aspect of the present application, a negative electrode current collector is provided, comprising the composite material described in any one of the first aspect of the present application, or a composite material prepared by the preparation method described in any one of the second aspect of the present application.

[0036] In a fourth aspect of the present application, a metal battery is provided, comprising the negative electrode current collector as described in any one of the third aspects of the present application.

[0037] In one embodiment, the metal battery has one or more of the following features:

[0038] (1) The thickness of the negative electrode current collector is 0.5 μm to 20 μm;

[0039] (2) The metal battery includes one or more of a lithium metal battery, a sodium metal battery and a potassium metal battery.

[0040] In a fifth aspect of the present application, there is provided an electrical device comprising the metal battery described in the third aspect of the present application.

[0041] The composite material provided by the present application has at least the following beneficial effects:

[0042] The composite material provided in the present application has good electrochemical properties when used as a negative electrode current collector. Specifically, the MXene material included in the composite material has good metallic conductivity, which can provide an effective electron transmission channel. At the same time, the MXene sheet carrying silver nanoparticles can further adjust the local electric field and chemical environment around the MXene material, so that the negative electrode active material such as lithium is more uniform during the deposition or extraction process, so as to promote the formation of uniform nucleation, thereby helping to reduce the battery performance degradation caused by violent local reactions such as the formation of lithium dendrites.

[0043] Furthermore, the intermolecular interaction between the oxygen-containing functional groups on the surface of the modified bacterial cellulose and the surface functional groups of the MXene material allows the modified bacterial cellulose and the MXene material to be composited with each other, which can further increase the mechanical properties of the negative electrode current collector and prevent the MXene material from stacking or structural collapse during the battery cycle. And the composite of modified bacterial cellulose and MXene materials can optimize the interface between the negative electrode current collector and the negative electrode active material. This good interfacial interaction can improve the adhesion of the negative electrode active material on the current collector, making it difficult for the negative electrode active material to fall off during the charge and discharge process, so as to ensure that the electrical contact between the negative electrode active material and the negative electrode current collector is always good, thereby improving the battery cycle performance.

[0044] In addition, the composite material provided in the present application has a flexible structure, which can meet the requirements of heterogeneous batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 XRD patterns of the MXene prepared in step (3), the bacterial cellulose in step (5), and the flexible current collector prepared in step (8) in Example 1 of the present application;

[0046] Figure 2 A digital image of the flexible current collector prepared in Example 1, and a thickness measurement image;

[0047] Figure 3 This is a scanning electron microscope image of the flexible current collector prepared in Example 1 of the present application;

[0048] Figure 4A nucleation overpotential test curve of an asymmetric battery assembled with a flexible current collector prepared in Example 1 of the present application;

[0049] Figure 5 This is a nucleation overpotential test curve of an asymmetric battery assembled with a flexible current collector prepared in Comparative Example 2 of the present application;

[0050] Figure 6 The Coulomb efficiency test curve of the flexible current collector prepared in Example 1 of the present application assembled into an asymmetric battery;

[0051] Figure 7 This is a cycle performance curve of a lithium symmetric battery assembled with the flexible current collector prepared in Example 1 of the present application. DETAILED DESCRIPTION

[0052] The following is a further complete and clear description of the composite material and its preparation method, negative electrode current collector, metal battery, and electrical device of the present application in conjunction with specific examples. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0053] In some special electronic products or devices, special-shaped batteries may be needed to meet the requirements of space and shape. For example, wearable devices such as smart watches and bracelets have limited internal space and irregular shapes. Flexible negative electrode current collectors can easily adapt to these special shapes, allowing the battery to be better embedded in the device and improve space utilization.

[0054] At present, there are main problems in the development of lithium metal negative electrodes. First, the electrochemical performance of lithium metal negative electrodes themselves is poor, and it is very easy to produce dendrites during the charging and discharging process, causing battery short circuit, low coulombic efficiency, short cycle life and other problems; second, in the electrode preparation process, the composite method of lithium metal and current collector is limited, and it is difficult to achieve flexible function due to the metal material of traditional current collector.

[0055] Based on this, the first aspect of the present application provides a composite material, comprising:

[0056] A MXene material comprising surface functional groups;

[0057] Silver nanoparticles, the silver nanoparticles are in-situ grown on the surface of the MXene material layer;

[0058] Modified bacterial cellulose, wherein the modified bacterial cellulose comprises bacterial cellulose and oxygen-containing functional groups modified on the surface of the bacterial cellulose; the modified bacterial cellulose is loaded on the surface of the MXene material;

[0059] Wherein, the loading method of the modified bacterial cellulose at least includes: intermolecular interaction between the oxygen-containing functional groups of the modified bacterial cellulose and the surface functional groups of the MXene material.

[0060] The composite material provided in the present application has good electrochemical properties when used as a negative electrode current collector. Specifically, the MXene material included in the composite material has good metallic conductivity, which can provide an effective electron transmission channel. At the same time, the MXene nanosheets carrying silver nanoparticles can further adjust the local electric field and chemical environment around the MXene material, so that the negative electrode active material such as lithium is more uniform during the deposition or extraction process, so as to promote the formation of uniform nucleation, thereby helping to reduce the battery performance degradation caused by violent local reactions such as the formation of lithium dendrites.

[0061] Furthermore, the intermolecular interaction between the oxygen-containing functional groups on the surface of the modified bacterial cellulose and the surface functional groups of the MXene material allows the modified bacterial cellulose and the MXene material to be composited with each other, which can further increase the mechanical properties of the negative electrode current collector and prevent the MXene material from stacking or structural collapse during the battery cycle. And the composite of modified bacterial cellulose and MXene materials can optimize the interface between the negative electrode current collector and the negative electrode active material. This good interfacial interaction can improve the adhesion of the negative electrode active material on the current collector, making it difficult for the negative electrode active material to fall off during the charge and discharge process, so as to ensure that the electrical contact between the negative electrode active material and the negative electrode current collector is always good, thereby improving the battery cycle performance.

[0062] In addition, the composite material provided in the present application has a flexible structure, which can meet the requirements of heterogeneous batteries.

[0063] In one example, the chemical formula of the MXene material is M n+1 X n T x , where M is a transition metal element, X is carbon or nitrogen, and T x is a surface functional group, n is 1, 2 or 3, and the surface functional group includes at least one of -OH, -F and =O.

[0064] MXene materials have a two-dimensional layered structure, and the chemical bond between M and X has a certain metallic property, which can realize the rapid transmission of electrons. In addition, MXene materials are obtained by etching MAX materials. Since A in MAX materials is removed, there will be a large number of dangling bonds and defects on the surface of M atoms that bond with A. The above dangling bonds and defects are the load of Ag, or Ag +The reduction of MXene provides active sites. In addition, the etched MXene material has a large number of surface functional groups, which enables it to better composite with modified bacterial cellulose.

[0065] Furthermore, in the MXene material, M includes but is not limited to Ti. For example, the MXene material includes Ti2CT x 、Ti3C2T x 、Ti3N4T x and Ti3CNT x One or more of .

[0066] In one example, in the composite material, the mass ratio of the MXene material to the modified bacterial cellulose is 10: (0.1-10). It is understandable that the mass ratio of the MXene material to the modified bacterial cellulose can be selected from any value between 10: (0.1-10). For example, the mass ratio of the MXene material to the modified bacterial cellulose includes but is not limited to 10: 0.1, 10: 0.5, 10: 1, 10: 1.5, 10: 2, 10: 3, 10: 4, 10: 5, 10: 6, 10: 7, 10: 8, 10: 9 or 10: 10.

[0067] In one example, in the modified bacterial cellulose, the oxygen-containing functional group includes at least one of -OH and =O.

[0068] In the present application, bacterial cellulose is modified with oxygen-containing functional groups such as -OH and =O, so that intermolecular interactions such as hydrogen bonds are achieved between the oxygen-containing functional groups in the modified bacterial cellulose and the surface functional groups of the MXene material, so as to achieve the composite of the modified cellulose and the MXene material.

[0069] A second aspect of the present application provides a method for preparing a composite material, comprising the following steps:

[0070] S10. Under stirring conditions, the MAX material is etched using an etchant to prepare a MXene solution.

[0071] S20, mixing the MXene solution and silver nitrate, allowing the silver ions to undergo a reduction reaction on the surface of the MXene material sheet, so that silver nanoparticles are in situ grown on the surface of the MXene material sheet, to prepare a silver-loaded MXene solution.

[0072] S30, modifying bacterial cellulose with an alkali solution to prepare a modified bacterial cellulose solution; wherein the surface of the modified bacterial cellulose includes oxygen-containing functional groups.

[0073] S40, mixing the silver-loaded MXene solution and the modified bacterial cellulose solution, so that the modified bacterial cellulose is loaded on the surface of the MXene material to prepare a composite material.

[0074] In one example, in step S10, the step of preparing the MXene solution further includes:

[0075] S100, mixing fluoride salt and hydrochloric acid to prepare the etchant.

[0076] In one example, in step S100, the mass volume ratio of the fluoride salt and the hydrochloric acid is 1 g: (10-20) mL. It is understandable that the mass volume ratio of the fluoride salt and the hydrochloric acid can be selected from any value between 1 g: (10-20) mL. For example, the mass volume ratio of the fluoride salt and the hydrochloric acid includes but is not limited to 1 g: 10 mL, 2 g: 10 mL, 5 g: 10 mL, 7 g: 10 mL, 9 g: 10 mL or 10 g: 10 mL.

[0077] In one example, in step S100, the molar concentration of the hydrochloric acid is 6 mol / L to 12 mol / L. For example, the molar concentration of the hydrochloric acid includes but is not limited to 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L, 10 mol / L, 11 mol / L or 12 mol / L.

[0078] In one example, in step S100, the fluoride salt includes one or more of lithium fluoride, sodium fluoride and potassium fluoride.

[0079] The present application found that the etchant prepared by fluoride salt and hydrochloric acid is more gentle on MAX materials than the etchant of hydrofluoric acid; in addition, the metal ions in the fluoride salt can enter between the sheets during the etching process, expanding the interlayer spacing, making it easier to separate the nanosheets during the peeling process. Therefore, the in-situ hydrofluoric acid etchant can not only increase the content of MXene nanosheets in the solution, but also obtain high-quality nanosheets, and ensure that the dangling bonds and defects on the surface of the M atoms on the nanosheets are exposed, thereby providing a load for Ag or Ag. + The reduction provides active sites.

[0080] In one example, in step S10, the chemical formula of the MAX material is M m+1 AX m , wherein M is a transition metal element, A is a main group element of group IIIA or group IVA, X is carbon or nitrogen; and m is 1, 2 or 3.

[0081] Illustratively, the MAX material is one or more of Ti2AlC, Ti3AlC2, Ti3AlN4 and Ti3AlCN.

[0082] To ensure the etching rate and the formation of dangling bonds and defects on the surface of M atoms. In one example, in step S10, the mass ratio of the fluoride salt included in the etchant to the mass ratio of the MAX material is 1: (0.8-1.5). For example, the mass ratio of the fluoride salt included in the etchant to the mass ratio of the MAX material includes but is not limited to 1: 0.8, 1: 0.9, 1: 1, 1: 1.1, 1: 1.2, 1: 1.3, 1: 1.4 or 1: 1.5.

[0083] In one example, in step S10, after the etching step, the process further includes: centrifuging and washing the mixed solution after the etching, collecting the solid phase, dispersing the solid phase in a dispersant, collecting the supernatant, and preparing the MXene solution.

[0084] In one example, the centrifugal washing conditions include: washing the mixed solution to a pH of 5-7.

[0085] In one example, the process parameters for dispersing the solid phase in the dispersant include: ultrasound for 1h~3h and a temperature of 5°C~20°C.

[0086] The mixed solution after etching is further centrifuged and washed, and the solid phase is collected, and then the solid phase is dispersed in a dispersant, which can remove metal ions in the fluoride salt and purify the MXene material.

[0087] To fully precipitate impurities and ensure the separation efficiency of the Mxene material. In one example, the process parameters for collecting the supernatant include: a centrifugal speed of 3000r / min~6000r / min, and a centrifugal time of 20min~40min. For example, the centrifugal speed includes but is not limited to 3000r / min, 3500 r / min, 4000 r / min, 4500 r / min, 5000 r / min, 5500 r / min or 6000 r / min. The centrifugal time includes but is not limited to 20min, 25 min, 30 min, 35 min or 40min.

[0088] To ensure Ag + The interaction with the dangling bonds and defects of M atoms promotes the Ag +Reduction on the surface of MXene material. In one example, in step S20, in the solution formed by mixing the MXene solution and silver nitrate, the mass concentration of the silver nitrate is 0.3 mg / mL~1 mg / mL. For example, in step S20, in the solution formed by mixing the MXene solution and silver nitrate, the mass concentration of the silver nitrate includes but is not limited to 0.3 mg / mL, 0.4 mg / mL, 0.5 mg / mL, 0.6 mg / mL, 0.7 mg / mL, 0.8 mg / mL, 0.9 mg / mL or 1 mg / mL.

[0089] In one example, in step S20, the process parameters of the reduction reaction include: a stirring speed of 50 r / min to 300 r / min. For example, in the reduction reaction, the stirring speed includes but is not limited to 50 r / min, 80 r / min, 100 r / min, 120 r / min, 140 r / min, 180 r / min, 200 r / min, 220 r / min, 250 r / min, 280 r / min or 300 r / min.

[0090] In one example, in step S30, the alkaline solution includes one or more of KOH and NaOH.

[0091] In one example, in step S30, the molar concentration of the alkali solution is 0.8 mol / L to 1.5 mol / L. For example, the molar concentration of the alkali solution includes but is not limited to 0.8 mol / L, 0.9 mol / L, 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L or 1.5 mol / L.

[0092] In one example, in step S30, the process parameters of the modification treatment include: the modification temperature is 40° C. to 90° C. For example, the modification temperature includes but is not limited to 40° C., 50° C., 60° C., 70° C., 80° C., 85° C. or 90° C. Further, the modification time includes but is not limited to 20 min to 40 min.

[0093] By limiting the process parameters such as the temperature and time of the modification treatment, as well as the molar concentration of the alkali solution, the surface of the bacterial cellulose after alkali solution treatment is loaded with abundant oxygen-containing functional groups, which can ensure that it forms intermolecular interactions such as hydrogen bonds with the surface functional groups of the MXene material, so that the MXene material and the modified cellulose attract each other and form a stable connection at the interface of the two materials.

[0094] In one example, in step S40, the ratio of the solid mass included in the silver-loaded MXene solution to the solid mass included in the modified bacterial cellulose solution is 10:(0.1-10). For example, the ratio of the solid mass included in the silver-loaded MXene solution to the solid mass included in the modified bacterial cellulose solution includes but is not limited to 10:0.1, 10:0.2, 10:0.5, 10:1, 10:2, 10:3, 10:4, 10:5, 10:6, 10:7, 10:8, 10:9 or 10:10.

[0095] In the preparation method provided in the present application, in coordination with the aforementioned steps and by limiting the process parameters of step S40, intermolecular interactions occur between the oxygen-containing functional groups of the modified bacterial cellulose and the surface functional groups of the MXene material, for example: the surface functional groups of the MXene and the functional groups on the bacterial cellulose can form hydrogen bonds, etc. At this time, the MXene nanosheets and the bacterial cellulose fibers aggregate to form a black gel mass, which further settles. After standing for a period of time, it can be clearly found that the solution is divided into two parts, namely, the upper part is a clear solution and the lower part is a gel mass. The formation of the gel mass not only promotes the separation of water and sediment, but also accelerates the dehydration process of the filtration process; at the same time, it avoids the stacking of the layers of the MXene nanosheets themselves, so that there are a large number of gaps in the thin film first formed on the surface of the filter membrane to ensure smooth subsequent dehydration.

[0096] In addition, when the above-mentioned layered solution is filtered and the sample is dried together with the filter membrane, the water-rich bacterial cellulose shrinks to a certain extent after losing water, so the prepared composite material will automatically fall off the filter membrane. Based on this feature, the difficulty of separating the composite material from the filter membrane is avoided.

[0097] In a third aspect of the present application, a negative electrode current collector is provided, comprising the composite material described in the first aspect of the present application, or a composite material prepared by the preparation method described in any embodiment of the second aspect of the present application.

[0098] It can be understood that the negative electrode current collector of the present application has all the advantages of the above-mentioned composite materials, so they are not repeated here. For example, the negative electrode current collector of the present application has good flexibility, lithium affinity, and light weight, which plays an important role in improving the energy density of metal batteries and expanding the application scenarios of negative electrode current collectors in heterogeneous batteries.

[0099] In a fourth aspect of the present application, a metal battery is provided, comprising the negative electrode current collector as described in any one of the third aspects of the present application.

[0100] Illustratively, the metal battery includes one or more of a lithium metal battery, a sodium metal battery, and a potassium metal battery.

[0101] In one example, the metal battery is an asymmetric battery. For example, the asymmetric battery includes a negative electrode current collector, a lithium metal sheet, and an electrolyte disposed between the negative electrode current collector and the lithium metal sheet. The lithium metal sheet serves as a lithium source. The negative electrode current collector is the negative electrode current collector shown in the third aspect of the present application.

[0102] In one example, the metal battery is a symmetrical metal battery containing a negative electrode. For example, the symmetrical metal battery containing a negative electrode includes a positive electrode sheet, a negative electrode sheet, and an electrolyte disposed between the positive electrode sheet and the negative electrode sheet. The positive electrode sheet and the negative electrode sheet of the symmetrical metal battery are configured with lithium metal of the same capacity. The negative electrode current collector is the negative electrode current collector shown in the third aspect of the present application.

[0103] In one example, the thickness of the negative electrode current collector is 0.5 μm to 20 μm. For example, the thickness of the negative electrode current collector includes but is not limited to 0.5 μm, 0.6 μm, 0.8 μm, 1 μm, 1.5 μm, 2 μm, 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, 15 μm, 17 μm, 18 μm or 20 μm.

[0104] The fifth aspect of the present application provides an electrical device, comprising the metal battery described in the fourth aspect of the present application.

[0105] The following further specific examples are provided to explain the present application in detail. It should also be understood that the following examples are only used to further explain the present application and cannot be understood as limiting the scope of protection of the present application. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present application belong to the scope of protection of the present application. The specific process parameters of the following embodiments are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not necessarily limited to the specific values ​​of the embodiments below.

[0106] Example 1

[0107] Embodiment 1 of the present application provides a negative electrode current collector and a preparation method thereof, comprising the following steps:

[0108] (1) Add 1 g of lithium fluoride to 15 mL of 9 mol / L hydrochloric acid to prepare an etchant.

[0109] (2) 1 g of Ti3AlC2 powder was slowly added to the etchant and etched at room temperature for 24 h. The mixed solution after etching was centrifuged and washed with deionized water until the pH reached 5. The solid phase was collected to prepare a layered MXene material. In the MXene material, since Al atoms were removed, many dangling bonds and defects were formed in the Ti atomic layer that was originally bonded to Al.

[0110] (3) The solid phase MXene material was dispersed in 100 mL of water, ultrasonicated in an ice bath (20 °C) for 3 h, and then centrifuged at 5000 r / min for 30 min. The supernatant was collected to prepare a MXene solution.

[0111] (4) 10 mL of MXene solution was measured and silver nitrate was added to prepare a mixed solution. The mass concentration of silver nitrate in the mixed solution was 0.5 mg / mL. The mixture was stirred for 30 min. The silver ions were reduced on the surface of the MXene material layer by utilizing the affinity of dangling bonds, defect sites and silver ions, thus in situ growing silver nanoparticles to prepare a silver-loaded MXene solution.

[0112] (5) The bacterial cellulose block is immersed in a 1 mol / L KOH solution and heated at 90°C for 30 minutes for modification. It is then repeatedly washed with deionized water at the same temperature until the pH is neutral. It is then put into a juicer and run for 15 minutes to obtain a modified cellulose solution.

[0113] (6) The silver-loaded MXene solution and the modified cellulose solution were mixed, wherein the ratio of the MXene solid content of the silver-loaded MXene solution to the modified cellulose solid content was 10:0.5, and stirred for 30 minutes. A hydrogen bond was formed between the OH of the modified bacterial cellulose and the surface functional groups of the MXene material, so that the modified bacterial cellulose was loaded on the surface of the MXene material. After the two were combined, a black gel mass was formed, which further precipitated. After standing for a period of time, it can be clearly found that the solution is divided into two parts, that is, the upper part is a clear solution and the lower part is a gel mass.

[0114] (7) The above-mentioned layered solution is filtered, and then the sample and the filter membrane are vacuum dried together at a temperature of 40°C for 8 hours. During the drying process, the water-rich bacterial cellulose shrinks to a certain extent after losing water, so the prepared flexible current collector will automatically fall off the filter membrane.

[0115] (8) After the above steps are completed, a flexible current collector can be obtained. The prepared flexible current collector is cut into discs of appropriate size and placed in a glove box for later use.

[0116] The XRD patterns of the MXene prepared in step (3) of Example 1, the bacterial cellulose prepared in step (5), and the flexible current collector prepared in step (8) are shown in FIG. Figure 1 The digital image of the flexible current collector prepared in Example 1 is shown in FIG. Figure 2 The scanning electron microscope image of the flexible current collector prepared in Example 1 is shown in Figure 3 shown.

[0117] Example 2

[0118] Embodiment 2 of the present application provides a negative electrode current collector and a preparation method thereof, comprising the following steps:

[0119] (1) 1 g of Ti3AlC2 powder was slowly added into 20 mL of 49 wt% HF solution and etched at room temperature for 6 h. The mixed solution after etching was centrifuged and washed with deionized water until the pH reached 5, and then the solid phase was collected.

[0120] (2) The solid phase MXene material was dispersed in 100 mL of water, ultrasonicated in an ice bath (10 °C) for 3 h, and then centrifuged at 3500 r / min for 30 min. The supernatant was collected to prepare a MXene solution.

[0121] (3) 10 mL of MXene solution was measured and silver nitrate was added to prepare a mixed solution. The mass concentration of silver nitrate in the mixed solution was 0.5 mg / mL. The mixture was stirred for 30 min. The silver ions were reduced on the surface of the MXene material layer by utilizing the affinity of dangling bonds, defect sites and silver ions, thus in situ growing silver nanoparticles to prepare a silver-loaded MXene solution.

[0122] (5) The bacterial cellulose was immersed in a 1 mol / L KOH solution and heated at 90°C for 30 minutes for modification. It was then repeatedly washed with deionized water at the same temperature until the pH was neutral. It was then put into a juicer and run for 15 minutes to obtain a modified cellulose solution.

[0123] (6) The silver-loaded MXene solution and the modified cellulose solution were mixed, wherein the MXene solid content in the silver-loaded MXene solution and the solid content in the modified cellulose were 10:0.5, and stirred for 30 minutes. A hydrogen bond was formed between the OH of the modified bacterial cellulose and the surface functional groups of the MXene material, so that the modified bacterial cellulose was loaded on the surface of the MXene material. After the two were combined, a black gel mass was formed, which further precipitated. After standing for a period of time, it can be clearly found that the solution is divided into two parts, that is, the upper part is a clear solution and the lower part is a gel mass.

[0124] (7) The above-mentioned layered solution is filtered, and then the sample and the filter membrane are vacuum dried together at a temperature of 40°C for 8 hours. During the drying process, the water-rich bacterial cellulose shrinks to a certain extent after losing water, so the prepared flexible current collector will automatically fall off the filter membrane.

[0125] (8) After the above steps are completed, a flexible current collector can be obtained. The prepared flexible current collector is cut into discs of appropriate size and placed in a glove box for later use.

[0126] Comparative Example 1

[0127] (1) Add 1 g of lithium fluoride to 15 mL of 9 mol / L hydrochloric acid to prepare an etchant.

[0128] (2) 1g Ti3AlC2 powder was slowly added to the etchant and etched for 24 hours. The mixed solution after etching was centrifuged and washed with deionized water until the pH reached 5, and the solid phase was collected to prepare MXene material. In the MXene material, since Al atoms were removed, many dangling bonds and defects were formed in the Ti atomic layer that was originally bonded to Al.

[0129] (3) The solid phase MXene material was dispersed in 100 mL of water, ultrasonicated in an ice bath (20 °C) for 3 h, and then centrifuged at 5000 r / min for 30 min. The supernatant was collected to prepare a MXene solution.

[0130] (4) 10 mL of MXene solution was measured and silver nitrate was added to prepare a mixed solution. The mass concentration of silver nitrate in the mixed solution was 0.5 mg / mL. The mixture was stirred for 30 min. The silver ions were reduced on the surface of the MXene material layer by utilizing the affinity of dangling bonds, defect sites and silver ions, thus in situ growing silver nanoparticles to prepare a silver-loaded MXene solution.

[0131] (5) The silver-loaded MXene solution was filtered, and then the sample and the filter membrane were vacuum dried at 40 °C for 8 h.

[0132] (6) After the above steps are completed, a flexible current collector can be obtained. The prepared flexible current collector is cut into discs of appropriate size and placed in a glove box for later use.

[0133] Comparative Example 2

[0134] (1) Add 1 g of lithium fluoride to 15 mL of 9 mol / L hydrochloric acid to prepare an etchant.

[0135] (2) 1g Ti3AlC2 powder was slowly added to the etchant and etched for 24 hours. The mixed solution after etching was centrifuged and washed with deionized water until the pH reached 5, and the solid phase was collected to prepare MXene material. In the MXene material, since Al atoms were removed, many dangling bonds and defects were formed in the Ti atomic layer that was originally bonded to Al.

[0136] (3) The solid phase MXene material was dispersed in 100 mL of water, ultrasonicated in an ice bath (20 °C) for 3 h, and then centrifuged at 5000 r / min for 30 min. The supernatant was collected to prepare a MXene solution.

[0137] (4) The bacterial cellulose was immersed in a 1 mol / L KOH solution and heated at 90°C for 30 minutes for modification. It was then repeatedly washed with deionized water at the same temperature until the pH was neutral. It was then put into a juicer and run for 15 minutes to obtain a modified cellulose solution.

[0138] (5) Mix the MXene solution and the modified cellulose solution, wherein the solid content in the MXene solution and the solid content in the modified cellulose are 10:0.5, and stir for 30 minutes. Hydrogen bonds are formed between the OH of the modified bacterial cellulose and the surface functional groups of the MXene material, so that the modified bacterial cellulose is loaded on the surface of the MXene material. After the two are combined, a black gel mass is formed, which further settles. After standing for a period of time, it can be clearly found that the solution is divided into two parts, that is, the upper part is a clear solution and the lower part is a gel mass.

[0139] (6) The above-mentioned layered solution is filtered and then the sample and the filter membrane are vacuum dried at 40°C for 8 hours.

[0140] (7) After the above steps are completed, a flexible current collector can be obtained. The prepared flexible current collector is cut into discs of appropriate size and placed in a glove box for later use.

[0141] Test Example 1

[0142] The negative electrode current collector, polypropylene separator and lithium metal sheet prepared in the embodiment and the comparative example were assembled into an asymmetric battery of Li||negative electrode current collector in a glove box protected by an inert atmosphere. The electrolyte used in the battery included: lithium salt LiTFSI and an organic solvent, wherein the concentration of the lithium salt was 1 mol / L, and the organic solvent was ethylene glycol dimethyl ether and 1,3-dioxolane in a volume ratio of 1:1.

[0143] Using 0.2 mA cm -2 The current density of the asymmetric battery was characterized by the nucleation overpotential. The results are shown in Figure 4 As shown. Figure 4 It can be seen that the flexible current collector of Example 1 of the present application has a nucleation overpotential of 45 mV when assembled into an asymmetric battery. This lower nucleation overpotential indicates that the smaller the energy barrier required for lithium nucleation on the substrate, the stronger the lithium affinity. Figure 5 It can be seen that the same 0.2 mA cm -2 The current density of the flexible current collector of Comparative Example 2 of the present application has a nucleation overpotential of 56 mV after being assembled into a lithium symmetric battery. The values ​​of nucleation overpotentials obtained from the tests of other embodiments and comparative examples are shown in Table 1.

[0144] Table 1

[0145]

[0146] The reversible deposition / stripping on the current collector is reflected by the Coulombic efficiency, for which 1 mA cm -2 The current density is deposited on the negative electrode current collector of Example 1 of the present application for 1 hour (discharge process), and then the active lithium is stripped from the negative electrode current collector (charge process). By default, the lithium stripping is complete when the charging voltage reaches 1V. The deposition / stripping efficiency on the current collector can be obtained by dividing the capacity obtained in the charging process by the capacity in the discharge process. The specific test data curve is shown in Figure 6 As shown. Figure 6 It can be seen that when the negative electrode current collector of Example 1 is used, the deposition and stripping process of lithium on the current collector has good reversibility, which can effectively reduce the formation of lithium dendrites.

[0147] Test Example 2

[0148] Based on the asymmetric cell of Test Example 1, 0.2 mA cm -2 The current density was 4.8 mAh cm deposited on the flexible current collector of Example 1. -2 The same electrolyte is used to assemble a lithium symmetric battery based on the composite lithium metal negative electrode.

[0149] The performance characterization of lithium symmetric batteries is a direct reflection of the performance of lithium metal negative electrodes prepared based on the current collector, and is an important step in testing whether the current collector meets the standards. The cycle performance of lithium symmetric batteries is tested, and the corresponding test results are as follows: Figure 7 As shown. Figure 7 It can be seen that the negative electrode current collector provided in Example 1 of the present application, after being assembled into a lithium symmetrical battery, has a current density of 1 mA cm -2 、1mAh cm -2 It showed good cycle performance under the test conditions.

[0150] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0151] The above-described embodiments only express several implementation methods of the present application, which is convenient for understanding the technical solution of the present application in detail, but it cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several modifications and improvements can be made, which all belong to the scope of protection of the present application. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided in the present application are all within the scope of protection of the claims attached to the present application. Therefore, the scope of protection of the patent of this application shall be based on the content of the attached claims, and the description can be used to interpret the content of the claims.

Claims

1. A composite material, characterized in that: include: A MXene material comprising surface functional groups; Silver nanoparticles, the silver nanoparticles are in-situ grown on the surface of the MXene material layer; Modified bacterial cellulose, the modified bacterial cellulose comprising bacterial cellulose and oxygen-containing functional groups modified on the surface of the bacterial cellulose; The modified bacterial cellulose is loaded on the surface of the MXene material; Wherein, the loading method of the modified bacterial cellulose at least includes: intermolecular interaction between the oxygen-containing functional groups of the modified bacterial cellulose and the surface functional groups of the MXene material.

2. The composite material according to claim 1, characterized in that The composite material has one or more of the following characteristics: (1) The general chemical formula of the MXene material is M n+1 X n T x , where M is a transition metal element, X is carbon or nitrogen, and T x is a surface functional group, n is 1, 2 or 3, and the surface functional group includes at least one of -OH, -F and =O; (2) In the composite material, the mass ratio of the MXene material to the modified bacterial cellulose is 10:(0.1-10); (3) In the modified bacterial cellulose, the oxygen-containing functional group includes at least one of -OH and =O.

3. A method for preparing a composite material, characterized in that: The following steps are involved: Under stirring conditions, the MAX material is etched with an etchant to prepare a MXene solution; The MXene solution and silver nitrate are mixed, and the silver ions undergo a reduction reaction on the surface of the MXene material sheet, so that silver nanoparticles are in situ grown on the surface of the MXene material sheet, thereby preparing a silver-loaded MXene solution; The bacterial cellulose is modified by an alkali solution to prepare a modified bacterial cellulose solution; wherein the surface of the modified bacterial cellulose includes oxygen-containing functional groups; The silver-loaded MXene solution and the modified bacterial cellulose solution are mixed, and the modified bacterial cellulose is loaded on the surface of the MXene material to prepare the composite material.

4. The method for preparing a composite material according to claim 3, characterized in that: The step of preparing the MXene solution further comprises: Mixing fluoride salt and hydrochloric acid to prepare the etchant; Wherein, the mass volume ratio of the fluoride salt and the hydrochloric acid is 1g: (10-20)mL.

5. The method for preparing a composite material according to claim 4, characterized in that: The steps of preparing the MXene solution have one or more of the following characteristics: (1) The fluoride salt includes one or more of lithium fluoride, sodium fluoride and potassium fluoride; (2) The molar concentration of the hydrochloric acid is 6 mol / L to 12 mol / L; (3) The general chemical formula of the MAX material is M m+1 AX m , wherein M is a transition metal element, A is a main group element of group IIIA or group IVA, X is carbon or nitrogen; m is 1, 2 or 3; (4) The mass ratio of the fluoride salt included in the etchant to the mass ratio of the MAX material is 1:(0.8-1.5); (5) After the etching step, the method further includes: centrifuging and washing the mixed solution after the etching, collecting the solid phase, dispersing the solid phase in a dispersant, collecting the supernatant, and preparing the MXene solution.

6. The method for preparing a composite material according to any one of claims 3 to 5, characterized in that: The step of preparing the silver-loaded MXene solution has one or more of the following characteristics: (1) In a solution formed by mixing the MXene solution and silver nitrate, the mass concentration of the silver nitrate is 0.3 mg / mL to 1 mg / mL; (2) The process parameters of the reduction reaction include: a stirring speed of 50 r / min to 300 r / min.

7. The method for preparing a composite material according to any one of claims 3 to 5, characterized in that: The step of preparing the modified bacterial cellulose solution has one or more of the following characteristics: (1) The alkali solution includes one or more of KOH and NaOH; (2) The molar concentration of the alkali solution is 0.8 mol / L to 1.5 mol / L; (3) The process parameters of the modification treatment include: the modification temperature is 40°C~90°C.

8. A negative electrode current collector, characterized in that: The invention comprises the composite material according to claim 1 or 2, or the composite material prepared by the preparation method according to any one of claims 3 to 7.

9. A metal battery, characterized in that: The negative electrode current collector according to claim 8 is included; the metal battery has one or more of the following characteristics: (1) The thickness of the negative electrode current collector is 0.5 μm to 20 μm; (2) The metal battery includes one or more of a lithium metal battery, a sodium metal battery and a potassium metal battery.

10. An electrical device, characterized in that: Comprising the metal battery as claimed in claim 9.

Citation Information

Patent Citations

  • Element-doped conductive composite carbonized material and preparation method and application thereof

    CN111725489A

  • Cellulose and transition metal carbon / nitride compounded three-dimensional current collector as well as preparation method and application thereof

    CN111952537A

  • MXene-doped and surface-coated modified lithium ion battery positive electrode material and preparation method thereof

    CN112331839A

  • Nanocellulose / MXene / silver nanowire sandwich structure composite film and preparation method thereof

    CN113072725A

  • MXene / silver nanowire / nanocellulose composite film and preparation method thereof

    CN113087972A

Cited By

  • Self-supporting flexible silver-rich electrode and preparation method and application thereof

    CN120341293A